DOI: 10.31274/rtd-180813-10531
|View full text |Cite
|
Sign up to set email alerts
|

Air mixing criteria for ceiling slot-ventilated agricultural enclosures

Abstract: This manuscript has been reproduced from the microfilm master. UMl films the text directly from the ori^al or copy submitted. Thus, some thesis and dissertation copies are in typewriter fece, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The conclusion of similarity analysis indicates that the possible similarity parameters for the isothermal airflow in an enclosure are geometry, Froude number, Euler number, jet momentum ratio, and Reynolds number between the model and the prototype (Yu, 1996). The Froude number is important for compressible flow and air-jet velocity, m/s u i air-jet velocity along the X axis, m/s u j air-jet velocity along the Y axis, m/s u t terminal velocity of the air-jet, m/s u d air-jet velocity at diffuser, m/s u ma- for motion with free liquid-vapour surfaces in the flow (Schlichting, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion of similarity analysis indicates that the possible similarity parameters for the isothermal airflow in an enclosure are geometry, Froude number, Euler number, jet momentum ratio, and Reynolds number between the model and the prototype (Yu, 1996). The Froude number is important for compressible flow and air-jet velocity, m/s u i air-jet velocity along the X axis, m/s u j air-jet velocity along the Y axis, m/s u t terminal velocity of the air-jet, m/s u d air-jet velocity at diffuser, m/s u ma- for motion with free liquid-vapour surfaces in the flow (Schlichting, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Model studies are practical for simulating the behaviour of a prototype and can be used to validate a numerical simulation. Similitude, or the relation between a model and prototype, is an important issue when using model studies (Yu, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions (high velocities or low temperature differences), the non-isothermal air-jets are dominated by Reynold's number or Euler's number. In a separate study, Yu (1996) reported that the non-isothermal air-jets behave similar to isothermal air-jets when the Ar was below 0.005 or corrected Archimedes number (ARc) was below 30 and the results agreed with those reported by Randall and Battams (1979). In addition, the lack of research on nonisothermal air-jet behavior in LBs adds to the difficulty in analyzing non-isothermal air-jets.…”
Section: Theoretical Backgroundsupporting
confidence: 52%
“…Leonard and McQuitty (1988) worked on a prototype animal building and reported that an ARc of five gave better inlet air-jet trajectories and air mixing, but also cautioned that confirming the results for large (commercial) animal buildings was needed. Yu and Hoff (2002) used LR scale-models to study the stability criteria for rooms fitted with slot inlets under nonisothermal conditions. The study reported that for ARc numbers above 75, two-circulation zones resulted implying that ARc numbers between 30 and 75 could be a good assumption for single-circulation air-jets desired in LRs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Yu (1996) found that the airflow pattern in a non-isothermal ceiling-slot ventilated enclosure can be defined by the Archimedes number which is modified from Mullejans (1966). In this paper, this modified Archimedes number is utilized to predict the airflow pattern: …”
Section: Experimental Processmentioning
confidence: 99%